Lower Urinary Tract and Pelvic Floor Symptoms and their Correlation with Fibroid Characteristics [39M]. (May 2018) - Shaffer, Robyn K.; Dobberfuhl, Amy D.; Fast, Angela M.; Vu, Kim-Nhiem; Ghanouni, Pejman; Chen, Bertha
Abstract : INTRODUCTION: Lower urinary tract symptoms (LUTS) are prevalent in women with uterine fibroids. Research suggests that increased fibroid volume and uterine bulk is associated with more severe LUTS and pelvic floor symptoms, however the correlation between fibroid size/location, adenomyosis, and symptoms has been under-studied. We sought to investigate this correlation using MRI which provides detailed information on fibroid characteristics. METHODS: A retrospective chart review was conducted for patients seen at the Stanford Fibroid Clinic. Patient demographics, medical history and pelvic MRI data were collected on 60 patients with completed Uterine Fibroid Symptom (UFS) and Pelvic Floor Distress Inventory (PFDI) validated symptom surveys. Primary outcome was scaled symptom scores and sub-scores including the Urogenital Distress Inventory (UDI-6). RESULTS: Dominant fibroid volume correlated negatively with urinary frequency (r=-0.307, P=.030), urgency (r=−0.287, P=.043), and pelvic pain or discomfort (r=-0.281, P=.049). Longest fibroid dimension also negatively correlated with UDI-6 (r=-0.304, P=.028). Number of fibroids and uterine volume were not significantly associated with LUTS. However, higher PFDI score was significantly associated with presence of adenomyosis on MRI (mean 82.9 vs 159.6, P=.018) and serosal fibroid location (mean 139.3 vs 69.0, P=.011). Patient BMI correlated positively with UDI-6 (r=0.415, P=.002) and PFDI (r=0.371, P=.005). CONCLUSION: Contrary to common belief, dominant fibroid size was inversely associated with LUTS, suggesting that fibroid dimensions may not predict bulk-related symptom severity. Adenomyosis should be considered in the evaluation of LUTS in women with uterine fibroids. In accordance with current literature, BMI is associated with LUTS including incontinence, urgency, and frequency.